THE REFORMULATION OF ALGORITHM FOR CALCULATING STAR’S POSITION AS THE SIGN OF ISYA AND FAJR PRAYER TIMES - Muhammad Syaoqi Nahwandi (Fakultas Syari'ah dan Hukum UIN Walisongo, 2019)
The position of the stars in the sky was used by Islamic Astronomy scholars as a sign of early Isya and Fajr prayers. This method is an alternative that was used in the past when there has not been an advanced time keeping tool like nowadays, especially for locations where syafaq and fajr shâdiq phenomena cannot be observed. Some of the algorithms used for calculating the star's position as a sign of early Isya and Fajr prayers are still fairly approximation (taqrîbi). So it requires a reformulation of the algorithm to make it is suitable for use in this period. This study resulted two offers of algorithms which are obtained by reformulating al-Buraidi’s method and al-Hâsib’s: First, the culmination of stars. Second, star’s altitude and azimuth. Accuracy test of reformulation of the algorithm compared by stellar observations shows that the results in reformulation of algorithm for calculating star’s position as the sign of early Isya and Fajr prayer time are quite accurate with accuracy in units of arc minutes.